Strategi Peningkatan Kesejahteraan Sosial Bagi Lanjut Usia di UPT PSTW Khusnul Khotimah Provinsi Riau - LESTARI, MIRANTY R.; KHAIRANI, TUTI (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
UPT PSTW Khusnul Khotimah is one of the organization in socialservices sector. The purpose of this research is to know and to analyze the strategyand also the factors wich influence the implementation of the strategy at UPTPSTW Khusnul Khotimah Riau Province to improve the welfare of the elderly.The teory concept of this research is organization strategy. It is consist of twoaspects, theh are innovation strategy and quality enhancement. The innovationstrategy can be seen from the implementation of working standards and thequality enhancement can be seen from the working valvation. This research usedqualitative methods with assessment the data descriptively. In collecting the data,the researcher used interview technique, observation, and documentation. Byusing the key informan as a source of information and triangulation technique as asource in examining the validation of the data. The result of this research showedthat the inplementation of enhancement strategy for the older persons welfare atUPT PSTW Khusnul Khotimah Riau Province is “good enough”. It can be seenfrom the older persons that can be handled at the UPT PSTW Khusnul KhotimahRiau Province only.Keyword: strategy, older persons, social welfare